Peritonitis following a bariatric procedure in a young woman. (14th February 2011) - Baigel, R; Rashid, F; Shrestha, D; Ravichandran, D
Abstract : A 22-year-old woman presented with generalised peritonitis from a gastric perforation due to erosion by an intragastric balloon inserted abroad 22 months previously in an attempt to help her lose weight. These balloons are of uncertain long-term benefit in obesity and should be removed after 6 months to avoid complications. This did not happen in this case; thus, leading to this life-threatening complication, which was treated with the removal of the balloon and omental patch repair of the perforation.